Associação entre nível maturacional e desenvolvimento físico em jovens atletas de futebol - Dias, José Valcy Rocha (Universidade Federal do Tocantins, 2022)
the study aimed to describe the maturational stage, physical growth and physical performance of young soccer players aged between 15 and 19 years old belonging to the base categories of the Tocantinópolis Esporte Clube in the city of Tocantinópolis in the state of Tocantins. Methods: It is characterized as a study with a quantitative approach, of the descriptive type. The sample was comprised of 50 young athletes athletes. Meeting the following inclusion criteria for students: age group between 15 and 19 years old, male. The instruments used were the Structured Questionnaire, Tanner's Maturation Stage (1980), Height, Scope Body Mass, Flexibility, Cardiorespiratory Fitness, Strength/Abdominal Endurance, Lower-limb Explosive Strength, Agility, Speed. Ethical procedures were adopted to carry out the research, such as: the research was only carried out after the soccer club authorized it by signing the consent letter, the students were previously informed about the objectives and procedures to be adopted and only those who were authorized by the guardians through the signing of the consent form participated, as well as the permission granted by the student through the assent letter. Results: About 40% indicated level 3 for pubic hair and 48% indicated level 4 for sexual organ maturational development according to Tanner (1980); in relation to physical fitness tests. The body mass of the young athletes had an average of just over 60 kilos and a BMI of 21.3, which are values considered normal, according to the WHO (2007), taking into account sex and age, the explosive strength of the lower limbs was greater than 190 centimeters on average, the wingspan had an average of just over 170 centimeters and the average agility of the volunteers in this research was around 6 seconds, the young players obtained an average above 1,072 meters in the aerobic resistance test, reaching an average around 27 centimeters in the flexibility test. Conclusion: Most Tocantinópolis Esporte Clube athletes have good levels of height and span, medium explosive strength of lower limbs, good levels of cardiorespiratory fitness and good flexibility, the levels of agility and speed are good, the maturational level of young athletes, was positively associated with flexibility and cardiorespiratory endurance.